Socio-cultural foundations of al-Farabi`s idea of “happiness” - Suleymenov, P.; Kassymbayev, K. (Journal of Oriental Studies, 2020)
The article examines the socio-cultural foundations of al-Farabi’s idea of “happiness” as a socio-cultural phenomenon from a scientific and theoretical point of view in detail. This phenomenon is directly related to the human soul, and each individual seeks to become a member of society, to achieve his level of personal perfection and, as a result, to achieve the main goal set for him. According to al-Farabi, all actions aimed at achieving happiness, at a certain stage, are formulated as social values. The concept of happiness underlies the socio-cultural foundations of al-Farabi. It is often said that this phenomenon is of great value to humans. Volunteering to achieve happiness is a wonderful thing to do. Morality and the habits that generate them are good things. Al-Farabi stressed that happiness is a great goal that everyone strives for, and happiness can be achieved only through knowledge and goodness. The main goal of education is personal improvement, and the main goal of a person’s existence in the world is defined as the achievement of happiness, which is recognized as the highest level of absolute goodness. Key words: knowledge, happiness, culture, virtuous city, ethics, personality, goodness, morality.